An Internet Service Provider’s Right of Discount Reimbursement Provided for the Customer in Case of Early Contract Termination - Totoraitis, Laurynas (Teisė, 2020)
The paper analyses the discounts offered to consumers in the agreements of Lithuanian Internet access service providers and the legal qualification of these discounts in the practice of the Communications Regulatory Authority and courts. The article raises the question of whether such discounts are not hidden penalties.
Keywords: consumer contract; discount attributes; hidden penalties; access to Internet contract